Modelling adoption of natural resources management technologies: the case of fallow systems in Benin - HONLONKOU, N'lédji Albert (My University, 2004)
This paper presents an adoption model of a resource management technology derived from a three-step decision process (information, adoption, and intensity of adoption). From the theoretical results it is found that while the levels of technical parameters such as duration and regeneration rate of soil fertility by improved fallow are relevant for adoption, it is misleading to ignore economic and social factors as they are reflected in the discount rate, risk, information, and prices of inputs and outputs. It is also shown that models that do not take account of the problems of self-selection due to the ability of the potential adopters to acquire and process the relevant information about a technology, lead to biased estimators. Empirical estimations generally confirm the theoretical results. It is found that the acquisition of information about resources management technology is influenced by age of farmers and actions of official extension services; the adoption decision is influenced by prior utilization, the bundle of land property rights owned, and the level of financial liquidity; and the intensity of adoption is influenced by the percentage of the farm that is degraded.
Keywords: Soil fertility; fallow system; Benin